2018
DOI: 10.1115/1.4039308
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Contribution of Vimentin to Cellular Stress Generation

Abstract: Contractile stress generation by adherent cells is largely determined by the interplay of forces within their cytoskeleton. It is known that actin stress fibers, connected to focal adhesions, provide contractile stress generation, while microtubules and intermediate filaments provide cells compressive stiffness. Recent studies have shown the importance of the interplay between the stress fibers and the intermediate filament vimentin. Therefore, the effect of the interplay between the stress fibers and vimentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
2
7
2
Order By: Relevance
“…Thus, depletion of vimentin filaments can cause instability of the microtubule network, thereby increasing contractility and traction forces (Figure S17B). This prediction agrees well with experimental studies in the literature for fibroblasts on stiff substrates where VIF -/-cells generate significantly higher forces compared with VIF +/+ cells (20)(21)(22). In contrast, microtubules in cells on soft substrates experience low co mpression, and therefore depletion of vimentin filaments does not cause significant instability in the microtubule network (Figure S17A).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, depletion of vimentin filaments can cause instability of the microtubule network, thereby increasing contractility and traction forces (Figure S17B). This prediction agrees well with experimental studies in the literature for fibroblasts on stiff substrates where VIF -/-cells generate significantly higher forces compared with VIF +/+ cells (20)(21)(22). In contrast, microtubules in cells on soft substrates experience low co mpression, and therefore depletion of vimentin filaments does not cause significant instability in the microtubule network (Figure S17A).…”
Section: Discussionsupporting
confidence: 90%
“…While the roles of the actin and microtubule networks in the generation and transmission of internal forces are known, it is not clear if and how intermediate filaments impact cellular forces. For example, experimental studies in the literature on fibroblasts, which are the most common cell type in connective tissues, report three different scenarios; upon depletion of vimentin intermediate filaments in fibroblasts, cell tractions forces have been observed (i) to decrease (17)(18)(19), (ii) to increase (20)(21)(22), or (iii) to remain the same (23). This discrepancy calls into question the role of vimentin intermediate filaments in the transmission of internally generated contractile forces to the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the method used to alter vimentin can influence the response, as described earlier by Charrier and Janmey [ 150 ]. Although a number of studies have indicated that vimentin is important for generation of contractile forces in cells [ 143 , 144 ], a recent study reported that the loss of vimentin increased the generation of contractile stress 3-fold [ 146 ]. Moreover, the viscous responses of cells have been suggested to depend upon vimentin [ 151 ].…”
Section: Vimentin: Functionmentioning
confidence: 99%
“…In particular, modification of the mechanical microenvironment resulted in a transient reduction in RPC adhesion and spreading capacity, a phenomenon described in other cell types [ 53 ]. Notably, recent studies have demonstrated that vimentin, which contributes to cells resilience against mechanical stress [ 54 ], generates with actin and microtubules the forces required for cell adhesion. More specifically, vimentin regulates stress generation by adherent cells through an interplay with actin stress fibers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%